The calibre effect on two traditional dry fermented sausages from Alentejo, Portugal, made from the same dough - Laranjo, Marta (2014)
Traditional food products are an important part of European gastronomy and it has been long empirically known that traditional fermented foods are vital to a good digestive health. However, and also due to health concerns, an extensive evaluation of food quality and safety parameters is crucial. Two low-salt dry-fermented sausages were manufactured from the same dough with two different casing calibres (small-“Catalão”/large-“Salchichão”) using two pig genotypes (Alentejano/Iberian x Duroc) and two NaCl concentrations (3%/5%). Three independent batches with replicates were prepared. The effects of calibre, genotype and salt concentration on the microbiological, physicochemical and textural parameters, as well as on sensory acceptability were considered. Analyses of variance were performed considering calibre, genotype and salt concentration. Regarding food safety of these traditional products, no Salmonella spp., Campylobacter spp. and Listeria monocytogenes, nor Enterobacteriaceae or in particular E. coli, were detected in the analysed products. Different numbers of lactic acid bacteria (LAB), enterococci and Micrococaceae were observed between the two calibres (p<0.05). Significantly different pH values were observed between genotypes and calibre (p<0.05). On the other hand, aw values differ significantly with salt (p<0.05). The Texture Profile Analysis (TPA) revealed significant differences between the two calibres regarding hardness, cohesiveness, resilience, gumminess and chewiness (p<0.05). Concerning the sensorial analysis, the calibre effect was sensed in the attributes succulence and tenderness (p<0.05). Salt differences were noted by panellists, but have minor impact on other studied parameters. Overall, the calibre effect was the most distinctive one, followed by the effect of genotype. Acknowledgements This work was supported by national funds through project PRODER 13.021 (QREN/PRODER/Medida 4.1), Fundação para a Ciência e a Tecnologia (FCT) under the Strategic Project PEst-OE/AGR/UI0115/2014 and co-funded by FEDER Funds through the COMPETE Programme. The authors thank PALADARES ALENTEJANOS Lda., A. Oliveira, G. Pias and R. Bicho for their collaboration.